Recent Advances in Characterization and Valorization of Lignin and Its Value-Added Products: Challenges and Future Perspectives - Shehbaz Ali; Abida Rani; Mudasir A. Dar; Muther Mansoor Qaisrani; Muhammad Noman; Kamaraj Yoganathan; Muhammad Asad; Ashenafi Berhanu; Mukul Barwant; Daochen Zhu (Biomass)
Lignin, the earth’s second-most abundant biopolymer after cellulose, has long been relegated to low-value byproducts in the pulp and paper industry. However, recent advancements in valorization are transforming lignin into a sustainable and versatile feedstock for producing high-value biofuels, bioplastics, and specialty chemicals. This review explores the conversion of lignin’s complex structure, composed of syringyl (S), guaiacyl (G), and p-hydroxyphenyl (H) units, into value-added products. We critically assess various biochemical and analytical techniques employed for comprehensive lignin characterization. Additionally, we explore strategies for lignin upgrading and functionalization to enhance its suitability for advanced biomaterials. The review emphasizes key areas of lignin valorization, including catalytic depolymerization methods, along with the associated challenges and advancements. We discuss its potential as a feedstock for diverse products such as biofuels, bioplastics, carbon fibers, adhesives, and phenolic compounds. Furthermore, the review briefly explores lignin’s inherent properties as a UV protectant and antioxidant, alongside its potential for incorporation into polymer blends and composites. By presenting recent advancements and case studies from the literature, this review highlights the significant economic and environmental benefits of lignin valorization, including waste reduction, lower greenhouse gas emissions, and decreased reliance on non-renewable resources. Finally, we address future perspectives and challenges associated with achieving large-scale, techno-economically feasible, and environmentally sustainable lignin valorization.